2021
DOI: 10.1002/kjm2.12431
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‐29b‐3p aggravates podocyte injury by targeting HDAC4 in LPS‐induced acute kidney injury

Abstract: Sepsis is a severe organ dysfunction disease, usually accompanied by acute kidney injury (AKI). miR-29b-3p was inhibited in sepsis-induced AKI, while its role in AKI was unclear. Therefore, this study determined the role of miR-29b-3p in sepsisinduced AKI, and investigated its underlying mechanism. In this study, the AKI model was established through injecting with lipopolysaccharides (LPS) intraperitoneally. In LPS challenged mice, serum blood urea nitrogen and creatinine were increased, and renal tissues pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have found that the expression of UPP1 is increased in the brain of sepsis rats [ 49 ]. HDAC4 (histone deacetylase 4) plays an important regulatory role in sepsis and may be an effective target for sepsis treatment [ 50 , 51 ]. The expression level of NARF (nuclear prelamin A recognition factor) in multiple sclerosis (a chronic neuroinflammatory disease) was increased [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the expression of UPP1 is increased in the brain of sepsis rats [ 49 ]. HDAC4 (histone deacetylase 4) plays an important regulatory role in sepsis and may be an effective target for sepsis treatment [ 50 , 51 ]. The expression level of NARF (nuclear prelamin A recognition factor) in multiple sclerosis (a chronic neuroinflammatory disease) was increased [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no data on the effect of sepsis on HDAC4 expression in skeletal muscle. However, LPS upregulates HDAC4 in mice podocyte cells MPC5 [ 59 ], and these authors concluded that HDAC4 mediates LPS-induced acute renal injury and podocyte injury. Furthermore, TMP195, an HDAC4 inhibitor, attenuates endotoxin-induced acute renal injury [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches confirmed that the LPS induces a significantly decreased expression of miR-29b in various cells. 36 38 For instance, study showed that compared to healthy individuals, miR-29b expression was reduced in the plasma of sepsis patients. LPS induced decrease expression of miR-29b in cardiomyocytes, and overexpression of miR-29b significantly alleviated the inflammatory in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%